A comparative study of intra-cervical foley’s catheter and PGE2 gel for induction of labour at term - Kanada, Anjali R.; Jain, Mahima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: In cervical ripening, before induction of labour, is needed to increase the success of labour induction, to reduce complications and to diminish the rate of caesarean section and duration of labour. Pharmacological preparations are in widespread use for cervical ripening but are not free from side-effects and complications. Mechanical methods, i.e. the use of Foley’s catheter balloon, though effective have not gained much popularity because of the fear of infection. Therefore, the study has been conducted to prove the efficacy and safety of extra amniotic Foley catheter balloon and to compare it with intra-cervical prostaglandin E2 (PGE2) gel. The objective of the study was to the success of induction of labor depends on the cervical status at the time of induction. For effective cervical ripening both Foley’s catheter and PGE2 gel are used. The aim of this study was to compare the efficacy of intra cervical Foley’s catheter and intra cervical PGE2 gel in cervical ripening for the successful induction of labor. Methods: A randomized, comparative study was conducted in the department of obstetrics and gynaecology, Civil hospital, B.J. Medical College Ahmedabad, during a period of 8 month from September 2018 to April 2019. 100 patients at term with a Bishop’s score ≤5 with various indications for induction were randomly allocated to group F (intra-cervical Foley’s catheter) and group P (PGE2 gel) with 50 women included in each group. Results: The groups were comparable with respect to maternal age, gestation age, indication of induction and initial Bishop’s score. Both the groups showed significant change in the Bishop’s score, 5.10±1.55 and 5.14±1.60 for Foley’s catheter and PGE2 gel, respectively, p <0.001. However there was no significant difference between the two groups. There was no significant difference in the side effects and caesarean section rate in both groups. The induction to delivery interval was 16.01±5.50 hours in group F and 16.85 ± 3.81 hours in group P (p=0.073). Apgar scores, birth weights and NICU admissions showed no significant difference between the two groups. Conclusions: The study shows that both Foley’s catheter and PGE2 gel are equally effective in pre induction cervical ripening.